CCAFS supports a 5-year (2018-2022) pan-African Climate Research for Development (CR4D) strategy that links climate research to agriculture for food security and resilience - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CCAFS engagement with Climate Research for Development (CR4D) shaped the program's focus on needs of African decision-makers, across time scales relevant to development and adaptation. CCAFS contributed to CR4D's initial agenda and launch; and its 2018 - 2022 Strategic Plan, which sets priorities and strategy to catalyze climate research that is responsive to development stakeholder needs at local, national and regional levels. It positions Africa's climate research community to better support climate services and climate-resilient development of Africa's agriculture sector.